Digital Farming as Direct of Digital Transformation State Policy - Strizhkova, Alla; Tokarieva, Kateryna; Liubchych, Anna; Pavlyshyn , Svitlana (European Journal of Sustainable Development, 2020)
Article is devoted considerations of digital agriculture as directly public policy. By authors it is considered terminological a variety of the studied phenomenon with which scientists of different specialties allocate an object of research. If at first among landowners arose and became settled the term "exact agriculture", then the names "E-Agriculture" and "digital farming" become even more relevant now, however in their work it is considered as synonyms. The essence and advantages of electronic agriculture, prospect revival of economic activity and efficiency of using technologies of digital agriculture and also a condition of legal regulation of digital agriculture in Ukraine are analyzed. Special relevance the idea of use of electronic agriculture in Ukraine enters in connection with plans of the Verkhovna Rada of Ukraine and the government to finish a land reform - to open the market of the land. Offers on further development of state regulation of digital agriculture are formulated. Keywords: computer aided farming, digital farming, digital transformation, digitalization, e-agriculture, precision agricuture, smart farming, state regulation